Unequal Efficacy of Different Infarct Location in Predicting Futile Recanalization of Patients With Acute Ischemic Stroke - Li, Zhao-shuo; Zhong, Hai-long; Zhou, Teng-fei; He, Ying-kun; Li, Qiang; Wang, Zi-liang; Zhu, Liang-fu; Wen, Chang-ming; Han, Jian-feng; Li, Tian-xiao (Frontiers in Neurology, 2022)
Objectives Endovascular thrombectomy (EVT) is a standard treatment for acute ischemic stroke (AIS) caused by large vessel occlusion, while futile recanalization is the main factor influencing the prognosis. The present study aimed to investigate the efficacy of different infarct sites in predicting futile recanalization of patients with AIS. Methods Data were obtained from two multicenter, prospective, randomized, and controlled trials, which were concurrently conducted in China. Cases achieving a successful recanalization and with complete data of preoperative Alberta Stroke Program Early CT score (ASPECTS) and 90-day follow-up were included. The ASPECTS subregions were used to mark different infarct locations in the two cerebral hemispheres. First, the distribution of each ASPECTS subregion in the left and right hemispheres and the whole brain was analyzed, respectively. Then, the regions associated with futile recanalization were initially assessed by a univariate model. Afterward, a multivariate logistic regression model was used to identify the efficacy of different infarct sites in predicting futile recanalization. Results A total of 336 patients were included in this study with a median age of 65 years (IQR: 51–74), of whom 210 (62.50%) patients were male, and 189 (56.25%) met the definition of futile recanalization. The correlation between each ASPECTS subregion and poor outcome was different when it was restricted to a specific cerebral hemisphere. Moreover, in the left hemisphere, the internal capsule region (OR: 1.42, 95%CI: 1.13–1.95, P = 0.03) and the M3 region (OR: 2.26, 95%CI: 1.36–3.52, P = 0.001), and in the right hemisphere, M6 region (OR: 2.24, 95%CI: 1.32–3.36, P = 0.001) showed significantly higher efficacy in predicting futile recanalization. Conclusion The efficacy of different infarct locations in predicting futile recanalization is different. Different preoperative patterns of the high-efficiency regions in the infarction core or penumbra can guide the thrombectomy decision-making.